Design of an Electrical Power Monitoring and Alert System Based on Internet of Things (IoT) for Chicken Coops - Supriyanto, Eko; Hasan, Abu; Pramuji, Tulus; Nurrani, Hanny (JAICT, 2025)
- The reliability of the electricity supply is a vital factor in ensuring the sustainability of modern poultry farming systems.Power outages or electrical disturbances can disrupt ventilation, heating, and lighting systems, resulting in decreased productivityon poultry farms. This study aims to design an Internet of Things (IoT)-based power supply detection and early warning system tomonitor electrical conditions in real-time and provide automatic notifications to farmers. The system was developed using aZMPT101B voltage sensor, an ACS712 current sensor, and a NodeMCU ESP8266 microcontroller, all of which are connected tothe Blynk platform for notification delivery. The research employed a prototyping approach, consisting of five stages: communication, planning, design, construction, and implementation. Testing was conducted in a closed poultry house located inWonolopo, Mijen, Semarang City. The results showed that the system was able to detect power disturbances with an accuracy rateof 97.6% and a notification response time of less than 3 seconds. The system proved effective in providing early warnings to farmers and enhancing the operational safety of electricity-based poultry farms.